Optimizing the Conditions for In Vitro Maturation and Artificial Activation of Sika Deer (Cervus nippon hortulorum) Oocytes. Issue 1 (28th March 2012) - Yin, Y; Tang, L; Zhang, P; Kong, D; Wang, Z; Guan, J; Song, G; Tang, B; Li, Z
Contents With the goal of establishing experimental protocols for cloning sika deer, various conditions for in vitro maturation (IVM) and artificial activation of sika deer oocytes were examined. In vitro maturation was evaluated in seven different culture media. The highest rate of oocyte maturation was 75.4% in 10 μg/ml follicle‐stimulating hormone (FSH), 1 μg/ml LH, 0.2 mm cysteamine and 50 ng/ml epidermal growth factor (EGF) after 24 h of IVM. The efficiency after 24 h of IVM did not differ significantly (p > 0.05) from that observed after 20 h. Cysteamine (0.2 mm) significantly increased the maturation rates after 20 h (from 59.1% to 67.2%, p < 0.05) and after 24 h (from 63.2% to 71.6%, p < 0.05) of IVM. The IVM rates of oocytes collected during the oestrous season (75.4%) and the anoestrous season (23.3%) were significantly different at 24 h. The 20 μg/ml FSH, 2 μg/ml LH, 0.4 mm cysteamine and 100 ng/ml EGF significantly increased the maturation rates (from 23.3% to 54.2%, p < 0.01) at 24 h during the anoestrous season. For the activation experiments, the most effective method was chemical activation [ionomycin + 6‐dimethylaminopurine (6‐DMAP)], which promoted the development of sika deer oocytes to the blastocyst stage (32.4%). Our results indicate that in vitro matured sika deer oocytes are good candidates for parthenogenetic activation and that chemical treatment is needed for relatively efficient activation of the oocytes. These optimized conditions for IVM and parthenogenetic activation may be useful for efforts to restore populations of the endangered sika deer using the somatic cell nuclear transfer technique.